Swimming in Physical Education of Children - Vladan M. Marković; Мiloš M. Milošević (Inovacije u Nastavi, 2022)
The aim of this paper is to examine the attitude towards the implementation of swimming in the teaching of physical and health education of children. The introduction of swimming as a mandatory program content of physical education is one of the possible innovations of this type which was the subject of the research and analysis of this paper. On the basis of theoretical analysis, “The Questionnaire on Swimming in Physical Education,” containing 17 statements which are answered via five-point Likert-type assessment scales was constructed. A total sample of 104 subjects, coaches, teachers of physical education and sport, active senior swimmers, and parents with children between the ages of six and ten were interviewed. The data on the socio-demographic characteristics, swimming, and sports habits were collected. The results of the descriptive statistical analysis and the reliability analysis by Crombach’s Alpha method (α = 0.75) indicate good metric characteristics of the questionnaire. The results of the descriptive statistical analysis show an extremely positive attitude of parents when it comes to swimming in physical education (M = 4.52, SD = 0.29). The descriptive statistical analysis supports the assumption that health and recreational goals of swimming (M = 4.81) are significantly ahead of sports and competition (M = 2.33). When it comes to assessing the emotions associated with swimming, it can also be concluded that recreation (M = 4.85) and entertainment (M = 4.66) are more important than competition (M = 3.72), i.e., that they provoke more positive emotions among children. The results of the variance analysis show that there are no statistically significant differences in attitudes towards swimming in physical education in the subsamples formed according to socio-demographic variables. The obtained results are primarily a confirmation of the positive educational and developmental effects of swimming. Furthermore, many problems exist with the realization of the idea of introducing swimming in regular classes. For such actions, the most important aspects include organization and cooperation of schools, sports centers and the local community, while the financial resources that need to be invested are not so great if the development benefits for children are taken into account. The observed extremely positive attitude of the subjects speaks to their readiness to help and support the implementation of such programs.